Composição gravimétrica e valorização econômica dos resíduos sólidos urbanos: estudo de caso na região central de Itacoatiara/AM - Guimarães, Gabriel dos Anjos (Brasil, 2019)
At present, the Itacoatiara municipality uses a still precarious solid waste management model, as presented in most Brazilian cities, where most of the waste produced is collected, without any type of segregation, and is directed to an inadequate final disposal. arranged in open dump with the presence of scavengers. One of the objectives established by the National Solid Waste Policy, sanctioned in 2010, is the recycling of waste, and among the instruments defined by it are the selective collection and the development of cooperatives and other forms of association of recyclable waste pickers. The objective of this study was to determine the recycling potential of municipal solid waste in neighborhoods of the central region of Itacoatiara, in the state of Amazonas, in order to subsidize the planning of actions that promote selective collection in the municipality. In the present study, the collection routes in the central region of the city were first identified and mapped. Then, two qualitative-quantitative characterizations of the residues (April / 2019 and May / 2019) from the study area were performed. In each sample, 2,400 liters of household waste from the collection routes were collected and then the quartering method was used to obtain the final sample of 600 liters, which was segregated and quantified, obtaining a gravimetric composition of the sample. In order to obtain the quantitative of the collected residues, the truck was weighed. In addition, we contacted the players involved in the recyclable materials market, in order to obtain the purchase and sale value of them and thus estimate the economic potential of the waste. It was possible to identify that the collection of waste from the central region is carried out by 3 collection routes, which cover 9 neighborhoods. According to the average gravimetric composition obtained, the percentage of the organic material represents around 51.32% of the mass of waste collected in the region, while the residues with recycling potential represent 37.40%, the wastes 4, 93% and other waste, 6.36%. The total mass generated per day in the central region was 14,910 kg (15 ton / day), with an annual generation of 5,442,150.00 kg / year (5,442 tons / year). As a result, an economic gain could be estimated from the sale of recyclable materials of R $ 361,200.35 per year if the collectors sold the materials collected to local buyers / companies and R $ 764,755.30 per year, if they were sold directly to buyers located in Manaus. Thus, the present study presents data that show the importance of selective collection in the region, where collecting and selling recyclable material is possible to obtain an economic gain and contribute to the reduction of the volume of these materials in the dump.